2002
DOI: 10.1002/jmv.10262
|View full text |Cite
|
Sign up to set email alerts
|

Genomes of the endothelial cell‐tropic variant and the parental Toledo strain of human cytomegalovirus are highly divergent

Abstract: The low-passage Toledo strain of human cytomegalovirus (HCMV) and fresh clinical HCMV isolates have been reported to share the capacity to propagate efficiently in endothelial cell cultures. In the laboratory, however, repeated attempts to adapt the Toledo strain to growth in endothelial cells have been unsuccessful. Southern blot analysis of the entire viral genome and restriction length polymorphism analysis of multiple genome regions amplified by PCR demonstrated that the reported endothelial cell-tropic vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In addition, both laboratory strains, currently considered to be Huv Ϫ Leuk Ϫ , were shown to be able to reacquire both properties, and thus to become Huv ϩ Leuk ϩ after adaptation to growth in HUVECs, as recently reported (9,10). In parallel, the Toledo strain (originally obtained from E. Gonczol, Wistar Institute), which is considered a low-passage wild-type HCMV strain, could never be adapted to growth in ECs despite repeated attempts and was thus considered Huv Ϫ Leuk Ϫ , whereas the reported EC-tropic variant (18) of Toledo was shown to be a different virus strain that possibly originated from a recombination event (2).…”
Section: Methodsmentioning
confidence: 79%
“…In addition, both laboratory strains, currently considered to be Huv Ϫ Leuk Ϫ , were shown to be able to reacquire both properties, and thus to become Huv ϩ Leuk ϩ after adaptation to growth in HUVECs, as recently reported (9,10). In parallel, the Toledo strain (originally obtained from E. Gonczol, Wistar Institute), which is considered a low-passage wild-type HCMV strain, could never be adapted to growth in ECs despite repeated attempts and was thus considered Huv Ϫ Leuk Ϫ , whereas the reported EC-tropic variant (18) of Toledo was shown to be a different virus strain that possibly originated from a recombination event (2).…”
Section: Methodsmentioning
confidence: 79%
“…These results suggested that it was probably only minor variations in the viral genome of the two strains that were responsible for the loss/reacquisition of the two biological properties. In addition, the Toledo strain, commonly considered a prototype of wild-type strains, was shown to lack both EC-and leuko-tropism [51].…”
Section: Hcmv Leukocyte and Endothelial Cell Tropismmentioning
confidence: 99%
“…At the beginning of this study, the following findings were critical in directing interest to the ULb¢ region as a prime candidate: (i) the loss of EC-and leuko-tropism in the laboratory strains, Towne and AD169, was associated with the loss of the great majority of ULb¢ [52,53]; (ii) the low-passaged strain Toledo, which was shown to be tropism-deficient [51], was found to display an inversion of ULb¢ [53]; and (iii) extensive propagation of EC-and leuko-tropic clinical isolates in HELFs was found to be consistently associated with the selection of tropism-deficient variants [37,45,[54][55][56] in the presence of only minor variations in the relevant viral genomes.…”
Section: Genetic Determinants Of Endothelial Cells and Leukocyte Tropismmentioning
confidence: 99%
“…Like AD169, it was passaged extensively in fibroblasts as a vaccine candidate. Toledo, isolated from the urine of a congenitally infected child (12); FIX (VR1814), isolated from a pregnant woman with a primary HCMV infection (13,14); PH, isolated from a bone marrow transplant patient (15,16); and TR, an ocular isolate from an AIDS patient with retinitis (17) (19).…”
mentioning
confidence: 99%